2013
DOI: 10.33590/emjdiabet/10310009
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Mellitus and Periodontitis: Signs of a Bidirectional Relationship

Abstract: Periodontitis is a multifactorial, irreversible and cumulative condition, initiated and propagated by bacteria and host factors. The multifactorial nature of periodontitis is related with the complex interactions between microorganisms in the microbial dental plaque and host response mechanisms, as well as environmental factors. Progression of periodontal disease is very much dependent on host response. Diabetes mellitus (DM), a complex metabolic disorder characterised by prolonged hyperglycaemia, has long bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 66 publications
0
1
0
Order By: Relevance
“…13 Periodontitis affects the onset and development of DM disease. 20 All prospective studies included in the systematic reviews reported a positive association between high glucose levels and the onset and development of periodontitis. There was an adequate 86% increase in the incidence or risk of developing periodontitis in uncontrolled diabetes compared with non-DM or people with well-controlled DM.…”
Section: Resultsmentioning
confidence: 99%
“…13 Periodontitis affects the onset and development of DM disease. 20 All prospective studies included in the systematic reviews reported a positive association between high glucose levels and the onset and development of periodontitis. There was an adequate 86% increase in the incidence or risk of developing periodontitis in uncontrolled diabetes compared with non-DM or people with well-controlled DM.…”
Section: Resultsmentioning
confidence: 99%